1985
DOI: 10.1128/mcb.5.4.721-727.1985
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Nascent Monkey DNA Synthesized Early in the Cell Cycle

Abstract: To study the structure and complexity of animal cell replication origins, we have isolated and cloned nascent DNA from the onset of S phase as follows: African green monkey kidney cells arrested in G1 phase were serum stimulated in the presence of the DNA replication inhibitor aphidicolin. After 18 h, the drug was removed, and DNA synthesis was allowed to proceed in vivo for 1 min. Nuclei were then prepared, and DNA synthesis was briefly continued in the presence of Hg-dCTP. The mercury-labeled nascent DNA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Nascent DNA enriched 103to 104-fold for sequences replicating early in S phase were obtained by purely physical and chemical methods and used to generate clones. Four clones of the first five we examined, orsi, ors2, ors4, and orsS, were shown to replicate preferentially early in S phase (21).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Nascent DNA enriched 103to 104-fold for sequences replicating early in S phase were obtained by purely physical and chemical methods and used to generate clones. Four clones of the first five we examined, orsi, ors2, ors4, and orsS, were shown to replicate preferentially early in S phase (21).…”
Section: Resultsmentioning
confidence: 95%
“…It has been shown that four of the first five ors fragments analyzed (orsi, ors2, ors4, and orsS) preferentially replicate early in S phase (21). In this communication, we describe the genomic frequency, the genomic distribution, and the snapback properties of 12 ors sequences.…”
mentioning
confidence: 94%
See 2 more Smart Citations